Disaster in Itî’s land the tragic social history of the Datû class in Leyte (1521-1622) - Borrinaga, Rolando O. (Journal of History, 2010)
The label “Leyte” comes from Ila Itî, meaning it “belongs to Iti”. It replaced the island’s older name, Abuyo, and seems to have been intended to memorialize the tragic fate of the datû (indigenous elite) family that extended hospitality to the early Spanish explorers who reached our shores (the expeditions of Magellan, Villalobos and Legazpi). The family’s descendants were exterminated in the wake of the Bankaw Revolt in 1621, a century after initial contact. This paper reconstructs the social history of the datû class in Leyte from the initial contact with the Magellan expedition in 1521, through the contacts with members of the Villalobos expedition in the 1540s and the Legazpi expedition in 1565. It will also look into their reactions to the early Spanish attempts to subjugate them, their accommodation of the new colonial order, and the price they paid for the loss of their old alliances with the Muslims in the south, until the tragic revolt in 1621.